Validation of a Novel Endoscopic Feature that Predicts Helicobacter pylori-negative Status: Does the Scratch Sign Reflect H. pylori Non-infection? - Jun-young Seo; Hyo-Jin Cho; Sang Jong Park; Ah Young Lee; Sang-Jung Kim; Ji Yong Ahn (Yong Chan Lee, 2023)
Background/Aims Identification of Helicobacter pylori infection status is necessary as H. pylori is associated with gastric malignancy. Recently, a red linear scrape-like appearance on the gastric mucosa, called the "scratch sign," was reported to be associated with H. pylori-negative gastric mucosal status. Herein, we aimed to validate the association between the scratch sign and H. pylori infection status. Methods The data of patients who underwent screening endoscopy at Bundang Jesaeng General Hospital between March 2023 and April 2023 were reviewed. Patients were classified as having an H. pylori current infection or non-infection status based on the results of rapid urease tests. Patients who had undergone H. pylori eradication therapy were excluded. Endoscopic features of the gastric mucosa were assessed using the Kyoto classification of gastritis. Results The scratch sign appeared more frequently in patients with non-infection than in those with current infection status (32.7% vs. 10.6%, respectively; P<0.001). Multivariate analysis showed that only the presence of sticky mucus was significantly associated with the presence of the scratch sign. Patient without the scratch sign had a higher prevalence of open-type atrophy, intestinal metaplasia, enlarged folds, and diffuse redness, which reflected a higher Kyoto score. Conclusions Presence of the gastric mucosal scratch sign, a novel endoscopic marker, is indicative of H. pylori-negative status and appears to be inversely correlated with the presence of sticky mucus. In addition to the Kyoto classification of gastritis, detection of the scratch sign may facilitate identification of the H. pylori infection status.